Video-based flipped learning in higher education: Effects on students' learning motivation, attitudes, and engagement - Mariam Haghegh; Arif Nugroho (UIN Raden Mas Said Surakarta, 2021)
In the recent years, flipped learning has become popular and been widely utilized as teaching approach to activate studentsâ€™ learning engagement, which is frequently used to reverse the conventional teaching. However, much more efforts are necessary to enrich the literature about its practices across different teaching and learning contexts. This study is at the cutting edge of examining the practice of flipped learning in higher education contexts; as well as exploring its effects on studentsâ€™ learning motivation, attitudes, and engagement. Data were collected using a questionnaire from 35 undergraduate students enrolled in â€œIntroduction of Educational Technologyâ€ course at a college of education, and the data were tested using 24-version IBM-SPSS linear regression. The results demonstrated that flipped learning strategy is a positive predictor for studentsâ€™ learning motivation (p-value 0.001 < 0.05), attitudes (p-value 0.007 < 0.05), and engagement (p-value 0.003 < 0.05). The results contribute to offering valuable insights for college stakeholders to enhance the efficacy of teaching and learning process, particularly for higher education curriculum designers to adapt to the current teaching approach. Instructional implication and research suggestions are provided based on the results of the study.